Distribution and Service Qquality to Customer Satisfaction in Cikal Wedding Planner - Muhamad Anggi F; Heny Hendrayati; Ratih Hurriyati (Green Publisher Indonesia, 2024)
If the public understands the importance of wedding organizers with public awareness, Cikal Wedding Planner is here to help the community in making a happiness, namely marriage. The purpose of this study is to determine the Effect of Distribution and Service Quality on Customer Satisfaction. This research was conducted at one of the Wedding Organizer companies in Bandung, namely Cikal Wedding Planner. This research was conducted with a quantitative approach, data collection using observation methods, interviews and also the distribution of questionnaires. The data obtained will be tested using SPSS 24. The results showed that the distribution variable did not affect customer satisfaction with a significant level of 0.842 > 0.05. And also the Service Quality variable has a calculated value = 0.010 > ttable = 1.984 with a signification level of 0.920 = 0.05, and it can be concluded that the Service Quality variable affects Customer Satisfaction. And Distribution and Service Quality simultaneously (together) have an influence on Customer Satisfaction.